Professional Communication Education: Culture, Digital Ethics, and AI for Indonesia Migrant Workers in Japan - Husna Nur Amalina; Dimas Adika; Marimin; Kennia Wikandhita; Juairiah Nastiti Sandyaningrum; Dedy Eka Timbul Prayoga; Eki Rovianto; Desy Setyaningrum; Rizka Adela Fatsena; Nanang Maulana Yoeseph; Hengky Ditya Nugroho (Lembaga Teewan Journal Solutions, 2026)
Indonesian migrant workers (PMI) in Japan often face professional communication barriers due to cultural differences, language barriers, and digital literacy requirements. This community service program aims to equip members of PERMA UTLLN Japan and Indonesian migrant workers with professional communication skills, cross-cultural communication skills, digital ethics, and the use of Artificial Intelligence (AI) through a mixed-method approach consisting of interactive webinars, case studies, and simulations via Zoom. Data from observations and discussions were evaluated using qualitative descriptive analysis techniques through thematic categorization. The program results demonstrated an increase in understanding of assertive communication in the workplace, a reduction in the risk of culture shock through the philosophy of omotenashi, and the acceleration of ethics-based digital literacy in utilizing AI as a communication assistant. In conclusion, the integration of communication training and applied technology literacy significantly enhances the adaptive capacity, career performance, and work-study balance of student-workers abroad. The novelty of this program lies in the reconstruction of an interdisciplinary training curriculum that simultaneously combines cross-cultural intelligence with practical AI skills—a new blend of competencies that has never been implemented in conventional migrant worker support programs.